Comparison analysis of the magnetic field and the magnetic force inside of an electromagnetic actuator with the use of an armature measuring sensor - Heyder, Andreas; Losch, T.; Meyer, Alexander Wilhelm; Abersfelder, Sandra; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
Common errors in electromagnetic actuators must be reduced in order to meet the increasing requirements in quality and manufacturing costs. In-line magnetic process control is a promising method to avoid a great number of errors in early stages of production. This paper displays the meaningful correlation between the magnetic field and magnetic force characteristics of a proportional magnet. For this investigation, an armature measuring sensor is developed and implemented into a magnetic field test bench, which enables the realization of a so called smart factory.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electromagnetic actuator; in-line measurement; magnetic process control; three-dimensional magnetic field measurement